Customer Loyalty Drivers in Golden Transport Services: Pendorong Loyalitas Pelanggan pada Layanan Jasa Transportasi Golden Transport - Muhammad Iqbal Alim El Hakim; Rofiq; Ahmad Hisyam Hisyam; Imelda Dian Rahmawati (Procedia of Social Sciences and Humanities, 2026)
General Background: Maintaining long-term consumer loyalty remains a critical challenge for service-oriented firms amidst intensifying market competition. Specific Background: The Indonesian car rental industry, exemplified by PT Golden Transport, faces significant pressure to manage shifting customer preferences while ensuring operational sustainability. Knowledge Gap: Existing scholarly literature displays inconsistency regarding the causal relationship between service quality and customer loyalty, necessitating further empirical investigation. Aims: This study analyzes the roles of service quality, customer satisfaction, customer relationship management (CRM), and customer experience in shaping loyalty within the vehicle rental sector. Results: Utilizing multiple linear regression on 108 consumers, the analysis reveals that all four independent variables positively and significantly correlate with customer loyalty. Notably, customer experience emerges as the most influential factor, while empathy in service and conflict resolution in CRM demonstrate substantial predictive values. Novelty: This research provides a comprehensive integrative framework by simultaneously evaluating these four distinct marketing dimensions within the specific context of Indonesia’s competitive transport rental business. Implications: PT Golden Transport and similar service providers are encouraged to prioritize personalized CRM strategies, employee empathy training, and superior customer experience initiatives to secure long-term brand dedication and enhance recommendation rates. Highlights: Customer experience serves as the primary driver for strengthening consumer brand commitment in rental services. Effective conflict resolution within relationship management systems directly fosters higher levels of recurring transaction behavior. Empathetic service delivery creates significant value perceptions that distinguish providers in crowded transportation markets. Keywords: Customer Loyalty, Service Quality, Customer Satisfaction, Relationship Management, Customer Experience